2017
DOI: 10.1093/cercor/bhx005
|View full text |Cite
|
Sign up to set email alerts
|

mGluR2 versus mGluR3 Metabotropic Glutamate Receptors in Primate Dorsolateral Prefrontal Cortex: Postsynaptic mGluR3 Strengthen Working Memory Networks

Abstract: The newly evolved circuits in layer III of primate dorsolateral prefrontal cortex (dlPFC) generate the neural representations that subserve working memory. These circuits are weakened by increased cAMP-K+ channel signaling, and are a focus of pathology in schizophrenia, aging, and Alzheimer's disease. Cognitive deficits in these disorders are increasingly associated with insults to mGluR3 metabotropic glutamate receptors, while reductions in mGluR2 appear protective. This has been perplexing, as mGluR3 has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
117
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(129 citation statements)
references
References 47 publications
11
117
1
Order By: Relevance
“…In schizophrenia, there is a decreased expression of GLT-1 in the hippocampus of postmortem brain samples (Shan et al, 2013) and prefrontal cortex of genotyped patients (Spangaro et al, 2012). The blockade of GLT-1 increased the tonic activation of presynaptic metabotropic glutamate receptors (mGluRs) (Fleming et al, 2011), some of which protect neurons from excessive excitability and regulate the functioning of working memory of rhesus macaques (Jin et al, 2018). It was also noted that agonist mGluR2/3 ameliorates symptoms of schizophrenic psychoses (Segnitz et al, 2009).…”
Section: Glutamate Systemmentioning
confidence: 99%
“…In schizophrenia, there is a decreased expression of GLT-1 in the hippocampus of postmortem brain samples (Shan et al, 2013) and prefrontal cortex of genotyped patients (Spangaro et al, 2012). The blockade of GLT-1 increased the tonic activation of presynaptic metabotropic glutamate receptors (mGluRs) (Fleming et al, 2011), some of which protect neurons from excessive excitability and regulate the functioning of working memory of rhesus macaques (Jin et al, 2018). It was also noted that agonist mGluR2/3 ameliorates symptoms of schizophrenic psychoses (Segnitz et al, 2009).…”
Section: Glutamate Systemmentioning
confidence: 99%
“…134,145 In contrast, mGluR2 are localized presynaptically, where they inhibit glutamate release. 146 Another critical regulator of feedforward cAMP–calcium signaling in newly evolved dlPFC layer III microcircuits is the phosphodiesterase, PDE4A, which catabolizes cAMP and is anchored to the spine apparatus by the scaffolding protein Disrupted in Schizophrenia (DISC1). 147,148 Importantly, inflammation can reduce PDE4A actions and detach it from DISC1 via MAP kinase-activated protein kinase 2 (MK2) signaling.…”
Section: Dynamic Network Connectivity Of Dlpfc Layer Iii: Unique Neurmentioning
confidence: 99%
“…For example, Tyszkiewicz et al (2004) demonstrated that group II mGluR activation increased post-synaptic glutamate ionotropic NMDA receptor currents in dissociated rat prefrontal cortex pyramidal neurons. As we learn more about receptor subcellular localization, and expand efforts to disambiguate subtype specific roles (mGluR2 versus mGluR3; Copeland et al, 2012;Jin et al, 2018;Wood et al, 2018), it should be possible to better explain how group II mGluRs can exert both inhibitory and excitatory actions. It remains to be tested whether in the mouse IC postsynaptic receptors may be a major mGluR2/3 component.…”
Section: Discussionmentioning
confidence: 99%